2004
DOI: 10.1016/j.physe.2004.06.048
|View full text |Cite
|
Sign up to set email alerts
|

Size effects on the melting of nickel nanowires: a molecular dynamics study

Abstract: The melting process of nickel nanowires are simulated by using molecular dynamics with the quantum Sutten-Chen many-body force field. The wires studied were approximately cylindrical in cross-section and periodic boundary conditions were applied along their length; the atoms were arranged initially in a face-centred cubic structure with the [0 0 1] direction parallel to the long axis of the wire. The size effects of the nanowires on the melting temperatures are investigated. We find that for the nanoscale regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(59 citation statements)
references
References 30 publications
2
52
1
Order By: Relevance
“…Chemical methods, in particular, solution routes, are widely used for the fabrication of nanoparticles and nanocomposites [16]. Their thermal properties have also been studied by computer simulations (Monte Carlo [17] and molecular dynamics [18][19][20][21]) and experimental techniques, such as transition electron microscopy, Mössbauer spectroscopy, small and wide angle X-ray diffraction as well as positron annihilation [6]. It has been found that at temperature T < T m , the lattice vibrations of Fe [22,23] and Co [24] nanocrystals increase, which drops their corresponding Debye temperatures D (D).…”
Section: Thermal Stability Of Nanocrystalline Magnetic Materialsmentioning
confidence: 99%
See 3 more Smart Citations
“…Chemical methods, in particular, solution routes, are widely used for the fabrication of nanoparticles and nanocomposites [16]. Their thermal properties have also been studied by computer simulations (Monte Carlo [17] and molecular dynamics [18][19][20][21]) and experimental techniques, such as transition electron microscopy, Mössbauer spectroscopy, small and wide angle X-ray diffraction as well as positron annihilation [6]. It has been found that at temperature T < T m , the lattice vibrations of Fe [22,23] and Co [24] nanocrystals increase, which drops their corresponding Debye temperatures D (D).…”
Section: Thermal Stability Of Nanocrystalline Magnetic Materialsmentioning
confidence: 99%
“…In terms of Lindemann s criterion, the root of atomic mean-square displacement of crystals increases with increasing T. When T approaches T m , reaches a fraction of atomic diameter h and melting occurs. Because increases with decreasing D, the needed thermal energy to promote nanocrystals to melt decreases as D is reduced, and hence T m (D) decreases [18][19][20][21].…”
Section: Thermal Stability Of Nanocrystalline Magnetic Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Molecular dynamics simulations have been used to study many phenomena associated with nanoparticles. Of particular interests are the geometric structure and energetics of nanoparticles of Au (Erkoc 2000;Shintani et al 2004;Chui et al 2007;Pu et al 2010), Ag (ElBayyari 1998;Monteil et al 2010), Al (Yao et al 2004), Fe (Boyukata et al 2005), Pb (Hendy & Hall 2001), U (Erkoc et al 1999) and of alloys such as NaMg (Dhavale et al 1999), Pt-Ni/Co (Favry et al 2011), Pt-Au (Mahboobi et al 2009), Zn-Cd (Amirouche & Erkoc 2003), CuNi/Pd (Kosilov et al 2008), Co-Sb as well as the behavior of nanoparticles during the melting or freezing process such as Au (Wang et al 2005;Bas et al 2006;Yildirim et al 2007;Lin et al 2010;Shibuta & Suzuki 2010), Na ), Cu Zhang et al 2009), Al (Zhang et al 2006), Fe (Ding et al 2004;Shibuta & Suzuki 2008), Ni (Wen et al 2004;Lyalin et al 2009;Shibuta & Suzuki 2010), Pd (Miao et al 2005), Sn (Chuang et al 2004;Krishnamurty et al 2006), Na-alloys (Aguado & Lopez 2005), Pt-alloys (Sankaranarayanan et al 2005;Yang et al 2009;Shi et al 2011), Au-alloys Yang et al 2009;Gonzalez et al 2011;Shi et al 2011) and Ag-alloys (Kuntova et al 2008;…”
Section: Introductionmentioning
confidence: 99%